Analisis Implementasi Pengelolaan Keuangan Desa di Desa Waluhu Kecamatan Bone Kabupaten Bone Bolango - Dikna Towalu; Rio Monoarfa; Ayu Rakhma Wuryandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to describe the management of village funds in rural development efforts in Waluhu Village, Bone District, Bone Bolango Regency. This research uses a descriptive qualitative method. The data collection technique used was in the form of interviews and using secondary data at the research site. The interview was conducted using 3 informants and 1 community leader, all of whom came from the Waluhu Village Government which runs the government. The results of the study found that in 2021 and 2022 the waluhu village government in village financial management started from the planning stages, administrative implementation, reporting, to accountability. in accordance with applicable laws and regulations The accountability carried out by the Waluhu Village government technically and administratively is good. Although in terms of good management, in terms of reporting it is not enough because it does not have digital information media, besides that there is also less accountability because the village government does not provide such an information board in the village office